DETERMINATION OF CUPRITE DENSITY BY ANALYSIS OF OXYGENOUS CUPPER - A. G. Anisovich; T. P. Urban; A. S. Buynitskaya (Литьë и металлургия)
The cuprite density (Cu2O cuprous oxide) as a part of an eutectic of oxygen copper was determined by X-ray diffraction and by metallographic way. It is shown that the size of density of 6,2 g/cm3, the most often met in the reference books, cannot be used for calculation of quantity of oxygen in the deformed copper. By the X-ray diffraction analysis it is found value of density equal 2,14 g/cm3. By the metallographic analysis, on the basis of determination of the area of cuprite in the eutectic phase, gives value of density of 3,3 g/cm3.